LEXICAL FEATURES OF ENGLISH ADVERTISEMENT TAGLINES DURING PRIME TIME - Gregorius Aditya Christianto (UC Journal: ELT, Linguistics and Literature Journal, 2020)
Advertisement language employs certain characteristics which make its usage unique so that it is interesting to explore. There are 2 research problems addressed in this study. The first is to classify and analyze lexical features which are contained in English advertisement taglines during prime time moment. The second is to figure out what triggers the dominant lexical features used in English advertisement taglines during prime time. The data were taken from English advertisement taglines during the period of prime time in any local television stations in Indonesia. This study used document analysis method and was categorized as a qualitative research. Six lexical features were proposed to classify and analyze the data, namely colloquial words, coinages, loanwords, use of verbs, use of adjectives, and frequent use of compounds. The results of the study were there are six lexical features used in English advertisement taglines during prime time and the most three dominant features are colloquial words with 40%, use of verbs with 28.57%, and use of adjectives with 18.57%. There is a similarity between three of them that all of them employ monosyllabic words so it makes easier to catch by the audiences.